Economía de la atención y visión maquínica: hacia una semiótica asignificante de la imagen - Celis Bueno (Hipertextos, 2019)
This article explores the relationship between images and power in the context of what has been called “the attention economy”. In this new productive model, human attention becomes a new mechanism for the production of surplus value and the reproduction of power relations. On the one hand, human attention becomes a source of information that is captured and transformed in a productive force. On the other hand, human attention is used as a source of statistical information about a given population, shifting from a disciplinary society (based on the individual) towards a control society (based on statistical analysis and governability). In this new stage of capitalist accumulation in which images are produced and processed algorithmically, the traditional categories used to understand the relationship between power and images become obsolete. This article suggests the concept of “asignifying images” as a way of explaining the relationship between power and images in contemporary capitalism. By displacing Deleuze and Guattari’s non-representational theory to the case of “machinic vision” (Virilio), this article defines an original framework from where to explain the role of images in contemporary capitalism.